Meeting the Challenge of Linguistic Diversity: A Comprehensive Approach to School Restructuring - Nancy L. Commins; Ofelia B. Miramontes; Adel Nadeau (Educational Considerations, 1999)
The theme of this special issue attests to the growing awareness that to be truly prepared for the 21st century, educators must be ready and able to address the needs of the increasing numbers of linguistically diverse students. In doing so, they will discover that while the challenges are many, these students bring a new richness to the communities in which they live and have had a positive impact on the schools they attend.